Investimentos em educação do capital humano na empresa Fras-le, indústria metal mecânica, sob a ótica dos funcionários e dos gestores - Gemelli, Silvana Fátima (My University, 2014)
In the present research the contribution of the investiments in education in the Human Being Capital to reach the competitive advantages, at Fras-le a friction materials manufacturer a metallurgical industry, located in Caxias do Sul RS was examined. This study is supported by three theoretical approaches: Knowledge; Intellectual Capital; Human Being Capital. The conjugation of these three theoretical perspectives assists in the understanding of the dynamic process of the contribution of the investiments in education in the Human Being Capital. This research was developed in four phases: first stage: secondary data-collecting from the company archives, second stage: questionnaire application to all employees benefited with the program of education from the organization; third stage: interviews half-structuralized next to the leaderships of the company; fourth stage: data analysis gotten in the previous phases through descriptive statistics, in function to specific objectives and content analysis. The obtained results showed the perceptions from employees and the leaderships about how much investment in education is made by the company, the relationship between education investment and competitive advantages, verification of dissemination and application from the acquired knowledge, as well as the verification of the education impacts in the intellectual capital.
A presente pesquisa examinou a contribuição dos investimentos na educação do Capital Humano para o alcance das vantagens competitivas, em indústria metalúrgica, fabricante de materiais de fricção, localizada em Caxias do Sul RS, a Fras-le, sob a ótica dos funcionários e dos gestores. O estudo é sustentado por três abordagens teóricas, conhecimento, capital intelectual e capital humano, sendo que a conjunção destas três vertentes permitiu entender o processo da contribuição dos investimentos na educação do Capital Humano na empresa Fras-le. A pesquisa foi desenvolvida em quatro fases. Na primeira etapa: coleta de dados secundários junto aos arquivos da empresa; na segunda etapa: aplicação de questionário a todos os funcionários beneficiados com o programa de educação da organização; na terceira etapa: entrevistas junto à gestão da empresa; na quarta etapa: análise dos dados obtidos nas fases anteriores através de estatísticas descritivas em função dos objetivos específicos e análise de conteúdo. Os resultados obtidos evidenciaram as percepções dos funcionários e da gestão quanto ao investimento em educação; a relação entre o investimento em educação e as vantagens competitivas; a aplicação e disseminação dos conhecimentos obtidos, bem como os impactos da educação no Capital Intelectual.
Keywords: Administração de empresas; Capital humano; Capital intelectual; Conhecimento e educação; Gestão de pessoas; Educação profissionalizante; Human being capital; Intellectual capital; Knowledge and education